Effect of Trataka (Yogic Visual Concentration) on the Performance in the Corsi-Block Tapping Task: A Repeated Measures Study - Swathi, P. S.; Bhat, Raghavendra; Saoji, Apar Avinash (Frontiers in Psychology, 2021)
Background and Objective: Attention and memory are essential aspects of cognitive health. Yogasanas, pranayama, and meditation have shown to improve cognitive functions. There has been no assessment of Trataka (yogic visual concentration) on working or on spatial memory. The present study was planned to assess the immediate effects of Trataka and of eye exercise sessions on the Corsi-block tapping task (CBTT). Methods: A total of 41 healthy volunteers of both genders with age 23.21 ± 2.81 years were recruited. All participants underwent baseline assessment, followed by 2 weeks of training in Trataka (including eye exercise). Each training session lasted for 20 min/day for 6 days a week. After completion of the training period, a 1-week washout period was given. Each participant then was assessed in two sessions in Trataka and in eye exercise on two separate days, maintaining the same time of the day. Repeated measure analysis of variance with Holm’s adjustment was performed to check the difference between the sessions. Results: Significant within-subjects effects were observed for forward Corsi span andforward total score (p < 0.001), and also for backward Corsi span (p < 0.05) and backward total score (p < 0.05). Post hoc analyses revealed Trataka session to be better than eye exercises and baseline. The eye exercise session did not show any significant changes in the CBTT. Conclusion: The result suggests that Trataka session improves working memory, spatial memory, and spatial attention.